2017
DOI: 10.1002/anie.201701280
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐Containing Amorphous Cobalt Sulfide Porous Nanocubes as High‐Activity Electrocatalysts for the Oxygen Evolution Reaction in an Alkaline/Neutral Medium

Abstract: A novel OER electrocatalyst, namely oxygen-incorporated amorphous cobalt sulfide porous nanocubes (A-CoS O PNCs), show advantages over the benchmark RuO catalyst in alkaline/neutral medium. Experiments combining with calculation demonstrate that the desirable O* adsorption energy, associated with the distorted CoS O octahedron structure and the oxygen doping, contribute synergistically to the outstanding electrocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
293
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(309 citation statements)
references
References 64 publications
16
293
0
Order By: Relevance
“…To determine the phase composition, BVC-A is subjected to X-ray powder diffraction (XRD) examination. [31] This deduction can be explicitly evidenced by the emergence of Bi 4 V 2 O 11 phase after the re-calcination of BVC-A at 650 8 8C( Supporting Information, Figure S7). [31] This deduction can be explicitly evidenced by the emergence of Bi 4 V 2 O 11 phase after the re-calcination of BVC-A at 650 8 8C( Supporting Information, Figure S7).…”
mentioning
confidence: 89%
“…To determine the phase composition, BVC-A is subjected to X-ray powder diffraction (XRD) examination. [31] This deduction can be explicitly evidenced by the emergence of Bi 4 V 2 O 11 phase after the re-calcination of BVC-A at 650 8 8C( Supporting Information, Figure S7). [31] This deduction can be explicitly evidenced by the emergence of Bi 4 V 2 O 11 phase after the re-calcination of BVC-A at 650 8 8C( Supporting Information, Figure S7).…”
mentioning
confidence: 89%
“…The main peak of MoS-CoS-Zn-1pot at 1.9 Å is associated with Zn-S peak, which is also significant in the ZnS spectrum. [48] The CoS coordination in MoS-CoS-Zn shifts to a lower R-position (1.80 Å), demonstrating that the main Adv. On the other hand, the main Zn K-edge peak in MoS-CoS-Zn is located at a lower value (1.6 Å), corresponding to Zn-N interatomic distance, and the other secondary FT peaks are not similar to those of MoS-CoS-Zn-1pot and ZnS.…”
Section: Doi: 101002/advs201900140mentioning
confidence: 99%
“…[1][2][3] However, a practical application of the technology is hampered by the sluggish kinetics (high overpotential) of the anodic oxygen evolution reaction (OER). [24][25][26][27][28] However, MX a Y b type materials are usually prepared by multi-step methods, including high-temperature sulfurization, selenization, phosphorization, nitridation, or N 2 plasma treatment. [7][8][9][10] However, the scarcity and the high cost of iridium/ruthenium impede their large-scale utilization in industry.…”
mentioning
confidence: 99%
“…[11][12][13] Diverse strategies have been developed to improve the OER performance of transition metal based materials. [24][25][26][27][28] The incorporation of a second element can optimize the electronic structure, create active sites, and facilitate the intermediate adsorption to achieve high electric conductivity, high exposure of active sites, and high intrinsic activity for decent electrochemical oxygen evolution performance. [23] Recent studies showed that transition metal based materials, MX a Y b (M = transition metal, X, Y=O, S, Se, N, and P), possess good OER performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation